HUBUNGAN KUALITAS LINGKUNGAN PERTEMANAN DENGAN KECENDERUNGAN PENGGUNAAN BAHASA NEGATIF PADA SISWA MAN 1 JAKARTA - Shahwa Ainnun Nisa; Deska Nurdi Nanda; Dania Putri Muthia; Aditya Andung Saputra; Syifa Fauziah; Haekal Nadhil Raziq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the quality of the friendship environment and the tendency to use negative language among students of MAN 1 Jakarta. This research employed a quantitative approach using a correlational method. The sample consisted of 87 students selected through simple random sampling. Data were collected using Likert-scale questionnaires measuring friendship environment quality and the tendency to use negative language. The collected data were analyzed through validity, reliability, normality, homogeneity, linearity, Kendall's Tau-b correlation, simple linear regression, and coefficient of determination tests. The findings indicated a significant positive relationship between the quality of the friendship environment and the tendency to use negative language, with a Kendall's Tau-b correlation coefficient of 0.248 and a significance value of 0.001. Furthermore, the coefficient of determination (R²) showed that the friendship environment contributed 9.6% to students' tendency to use negative language, while the remaining 90.4% was influenced by other factors beyond this study. These findings suggest that a close friendship environment may encourage the use of negative language as an expression of intimacy rather than hostility.